Miravirsen (SPC3649) can inhibit the biogenesis of miR-122. Issue 1 (24th September 2013) - Gebert, Luca F. R.; Rebhan, Mario A. E.; Crivelli, Silvia E. M.; Denzler, Rémy; Stoffel, Markus; Hall, Jonathan
Abstract: MicroRNAs (miRNAs) are short noncoding RNAs, which bind to messenger RNAs and regulate protein expression. The biosynthesis of miRNAs includes two precursors, a primary miRNA transcript (pri-miRNA) and a shorter pre-miRNA, both of which carry a common stem-loop bearing the mature miRNA. MiR-122 is a liver-specific miRNA with an important role in the life cycle of hepatitis C virus (HCV). It is the target of miravirsen (SPC3649), an antimiR drug candidate currently in clinical testing for treatment of HCV infections. Miravirsen is composed of locked nucleic acid (LNAs) ribonucleotides interspaced throughout a DNA phosphorothioate sequence complementary to mature miR-122. The LNA modifications endow the drug with high affinity for its target and provide resistance to nuclease degradation. While miravirsen is thought to work mainly by hybridizing to mature miR-122 and blocking its interaction with HCV RNA, its target sequence is also present in pri- and pre-miR-122. Using new in vitro and cellular assays specifically developed to discover ligands that suppress biogenesis of miR-122, we show that miravirsen binds to the stem-loop structure of pri- and pre-miR-122 with nanomolar affinity, and inhibits both Dicer- and Drosha-mediated processing of miR-122 precursors. This inhibition may contribute to the pharmacological activity of the drug in man.